Assessing electron transfer reactions and catalysis in multicopper oxidases with operando X-ray absorption spectroscopy - Macedo, Lucyano J. A. (Nat Commun, 2020)
Here we propose an experimental setup based on operando X-ray absorption spectroscopy (XAS) to understand why copper-containing oxidoreductase enzymes show exceptional performance as catalysts for the oxygen reduction reaction (ORR). An electrode based on carbon nanoparticles organized in mesoporous structures with bilirubin oxidase (BOD) was developed to be used in a home-made operando XAS electrochemical cell, and we probed the electron transfer under ORR regime. In the presence of molecular oxygen, the BOD cofactor containing 4 copper ions require an overpotential about 150 mV to be reduced as compared to that in the absence of oxygen. A second electron transfer step, which occurs faster than the cofactor reduction, suggests that the cooper ions act as a tridimensional redox active electronic bridges for the electron transfer reaction.